Blockchain for Health IoT: A privacy‐preserving data sharing system. (15th June 2022) - Chen, Songling; Fu, Xiangling; Si, Hongchao; Wang, Yi; Gao, Songfeng; Wang, Chunyuan
Abstract: Health Internet of Things (Health IoT) has been limited by isolated information and a lack of security. As the combination of blockchain and Health IoT could potentially address these two limitations, it has attracted significant interest. However, blockchain‐based systems often fail to balance data sharing and privacy protection. Therefore, we proposed a Health IoT‐based privacy‐preserving data sharing blockchain system. We designed a privacy‐preserving method based on the content extraction signature scheme to enable patients to establish fine‐grained privacy protection. We designed a Byzantine fault‐tolerant leader election mechanism that enhances the security of the Raft algorithm while providing efficiency in the data sharing. Furthermore, we designed a summary contract to ensure efficient data retrieval. The proposed mechanism was evaluated in terms of the efficiency and security. The simulation and analysis results demonstrate that our scheme offers a secure and effective technique for achieving privacy‐preserving and efficient sharing of IoT medical data.